The technical infrastructure of dialysis centres as part of the price of health services - Dryl-Rydzyńska, Teresa; Książek, Piotr (Polish Journal of Public Health, 2012)
Introduction. A healthcare provider, operating in frames of the general healthcare insurance is required by law to have a certain technical infrastructure. Thus, the technical infrastructure is an essential component of a healthcare service. The condition of infrastructure components determines the safety and quality of the healthcare services.Aim. Definition of all the cost elements of technical infrastructure on the basis of a model of the average Polish dialysis centreMaterial and methods. Basing on data from literature and my own data obtained from 73 dialysis centres belonging to the Fresenius Nephrocare Polska Group, and the previously elaborated theoretical model of the haemodialysis centre, I have presented the constituents of the technical infrastructure of a dialysis centre from a cost perspective.Results. The components of the costs of daily handling the building infrastructure and monitoring the technical condition of medical apparatuses have been discussed in detail. The sources of financing of the technical infrastructure of dialysis centre have also been presented.Conclusions. Changes in the rules of financing health services under common health insurance, so as to include all of the components necessary to provide the service, including the necessary technical infrastructure, are a matter of fundamental importance. Without it, it will not be possible to carry out an economic reform of hospitals – irrespective of the legal form under which they function.